2022
DOI: 10.5194/nhess-2022-182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A methodological framework for the evaluation of short-range flash-flood hydrometeorological forecasts at the event scale

Abstract: Abstract. This paper presents a methodological framework designed for the event-based evaluation of short-range hydro-meteorological ensemble forecasts, in the specific context of an intense flash-flood event characterized by high spatio-temporal variability. The proposed evaluation adopts the point of view of end-users in charge of the organization of evacuations and rescue operations at a regional scale. Therefore, the local exceedance of discharge thresholds should be anticipated in time and accurately loca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Contingency tables are usually filled by combining a continuous temporal sequence of forecasts, at one single site and for one unique lead time. However, we followed here the principle proposed by Charpentier-Noyer et al (2022) to build the contingency tables by aggregating the forecasts issued during the most critical phase of the event (i.e. the forecasts issued during the flood rising limb, just before the threshold exceedance by Q sim , independently of the lead time).…”
Section: Verification Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Contingency tables are usually filled by combining a continuous temporal sequence of forecasts, at one single site and for one unique lead time. However, we followed here the principle proposed by Charpentier-Noyer et al (2022) to build the contingency tables by aggregating the forecasts issued during the most critical phase of the event (i.e. the forecasts issued during the flood rising limb, just before the threshold exceedance by Q sim , independently of the lead time).…”
Section: Verification Methodsmentioning
confidence: 99%
“…However, the POFD score is sensitive to the extent of the verification area, which directly determines the number of correct rejections (see figure 6). The choice of the verification area was already identified as an important issue by Charpentier-Noyer et al (2022) who suggested to pay a particular attention to the choice of the "HFA" (Hydrological Focus Area). For that reason, we chose to summary the contingency tables based on the Critical Success Index (CSI = a a+b+c ) instead of POD/POFDs.…”
Section: Verification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…La méthode d'évaluation appliquée porte sur la capacité de la chaine de prévision à anticiper les dépassements de seuils de débits de périodes de retour 2, 5 et 10 ans, pour huit événements de crues soudaines récents (entre 2019 et 2021) qui ont été rejoués. L'évaluation se base sur l'utilisation de tableaux de contingence et leur représentation cartographique, suivant la méthode proposée par M. Charpentier-Noyer et al [5] qui a été légèrement adaptée ici, ainsi que sur le calcul de scores synthétiques (Critical Success Index). Il est important de noter que cette évaluation, bien que basée sur des scores statistiques classiques, ne permet pas de caractériser la performance des prévisions sur de longues chroniques temporelles, mais simplement de regarder leur capacité à prédire correctement des événements spécifiques de forte intensité.…”
Section: La Méthode D'évaluationunclassified